2013
DOI: 10.1002/jcph.133
|View full text |Cite
|
Sign up to set email alerts
|

Population Pharmacokinetic Analysis of Linezolid in Low Body Weight Patients with Renal Dysfunction

Abstract: Linezolid has antibacterial activity against aerobic Gram-positive cocci, including methicillin-resistant Staphylococcus aureus (MRSA). Adjustment of the dose of linezolid has been proposed to be unnecessary in patients with reduced renal function. However, platelet counts and hemoglobin levels were shown to be significantly lower in such patients than in patients with normal renal function. The population pharmacokinetic (PPK) of linezolid was investigated in MRSA infected patients with renal dysfunction. Lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
50
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(54 citation statements)
references
References 19 publications
(32 reference statements)
4
50
0
Order By: Relevance
“…The intra-individual variability for V was fixed as 0 because it was very small (Á < 0.0025). Regarding CL, CL Cr was identified as the only covariate that significantly explained interindividual variability, whereas variability due to other unknown factors still remained (CV CL = 30.5%; Table 2) and was similar to previously reported values (CV CL = 31.3% [31] and 35.2% [20]). All relative standard error (standard error/estimate, %) values via the covariance step in NONMEM modelling were <23%, and all parameter estimates were in the range of the 95% CI using the bootstrap method.…”
Section: Resultssupporting
confidence: 87%
“…The intra-individual variability for V was fixed as 0 because it was very small (Á < 0.0025). Regarding CL, CL Cr was identified as the only covariate that significantly explained interindividual variability, whereas variability due to other unknown factors still remained (CV CL = 30.5%; Table 2) and was similar to previously reported values (CV CL = 31.3% [31] and 35.2% [20]). All relative standard error (standard error/estimate, %) values via the covariance step in NONMEM modelling were <23%, and all parameter estimates were in the range of the 95% CI using the bootstrap method.…”
Section: Resultssupporting
confidence: 87%
“…In contrast to the presence of ARDS and lactate, the cofactors weight, creatinine clearance, and impairment of liver function were described previously (15,(18)(19)(20)(21)(22)(23)(24)(25) (Fig. 4).…”
Section: Discussionmentioning
confidence: 78%
“…Several predictors, such as glomerular filtration rate (14,(18)(19)(20)(21)(22), body weight (18,(21)(22)(23)(24)(25), parameters of liver function (15,18,20), renal replacement therapy (15), and comedication such as rifampin (a potent P-glycoprotein inducer) (7), have already been described. However, the effects of other possible covariates, such as the presence of acute respiratory distress syndrome (ARDS), peritonitis, and single nucleotide polymorphisms of the P glycoprotein, remain unclear.…”
mentioning
confidence: 99%
“…Furthermore, the Cmin of linezolid was similar between the wound exudate and serum. Previous studies investigating the pharmacokinetics of linezolid in patients have shown that changes in the renal function significantly affect the pharmacokinetics of linezolid (7,17). The present patient's glomerular filtration rate increased from 5.7 to 11.5 mL/min/1.73 m 2 during the administration of linezolid, which may have induced the small variations observed in the Cmin of linezolid after the daily dose of linezolid was changed from 600 to 300 mg/day.…”
Section: Discussionmentioning
confidence: 45%
“…However, several studies have reported a correlation between thrombocytopenia and linezolid overexposure in patients with renal dysfunction (6)(7)(8)(9). Furthermore, the prolonged use of linezolid has been shown to induce adverse hematological events (10,11).…”
Section: Introductionmentioning
confidence: 99%